A guide to qualitative field research - Bailey, Carol A. 1950- (SAGE Publications, Inc., 2018)
A Guide to Qualitative Field Research provides readers with clear, practical, and specific instructions for conducting qualitative research in the field. In the expanded Third Edition, Carol A. Bailey gives increased attention to the early and last stages of field research, often the most difficult: selecting a topic, deciding upon the purpose of your research, and writing the final paper, all in her signature reader-friendly writing style. This edition features research examples from graduate and undergraduate students to make examples meaningful to fellow students; a new "Putting It All Together" feature, with examples of how different parts of the research process interact; and more emphasis on the "nuts and bolts" of research, such as what to include in an informed consent form, a proposal, and the final paper.